Disruptive Harmony: Why Classical Music Impairs Attention In Smartphone-Addicted Students - Mutmainnah Mutmainnah; Sukma Ainul Fitri; Dita Padiani Rahma; Wilis Srisayekti; Yanti Rubiyanti; Anissa Lestari Kadiyono; Marina Sulastiana; Neni Komalasari (Psikostudia : Jurnal Psikologi, 2026)
Excessive smartphone use among university students has been linked to a decline in cognitive control, particularly in the aspect of attention. The use of classical music is often considered a strategy for enhancing attention, yet its effectiveness in individuals with digital addiction still requires empirical testing. This study aims to determine the effect of classical music (Mozart K. 448) on the attention of students experiencing smartphone addiction. This experiment employed a two-group posttest-only design involving 60 students selected through purposive sampling. Attention was measured using a time-based Stroop Test (ms). The Mann-Whitney U test results showed a significant difference between the two groups (Z = -3.713; p < .001). The experimental group had a higher mean rank for reaction time (38.87) compared to the control group (22.13). These findings indicate that classical music acts as a cognitive distraction that decreases attention in students with smartphone addiction; therefore, the use of background music should be considered selectively.Penggunaan Smartphone yang berlebih pada mahasiswa telah dikaitkan dengan penurunan kontrol kognitif, khususnya pada aspek atensi. Pengguna musik klasik sering kali dianggap sebagai strategi dalam meningkatkan atensi, namun efektivitasnya pada individu dengan adiksi digital masih memerlukan pengujian empiris. Penelitian ini bertujuan untuk mengetahui pengaruh musik klasik (Mozart K. 448) terhadap atensi mahasiswa yang mengalami adiksi smartphone. Eksperimen ini menggunakan two-group posttest-only design terhadap 60 mahasiswa yang dipilih melalui purposive sampling. Atensi diukur menggunakan Stroop Test berbasis waktu (ms). Hasil uji Mann-Whitney U menunjukkan perbedaan signifikan antara kedua kelompok (Z = -3.713; p <.001). Kelompok eksperimen memiliki mean rank waktu reaksi lebih tinggi (38.87) dibandingkan kontrol (22.13). Temuan ini menunjukkan bahwa musik klasik merupakan distraksi kognitif yang menurunkan atensi pada mahasiswa dengan adiksi smartphone sehingga penggunaan musik latar perlu dipertimbangkan secara selektif.